2018
DOI: 10.1164/rccm.201705-0943oc
|View full text |Cite
|
Sign up to set email alerts
|

Features and Outcomes of Methamphetamine-associated Pulmonary Arterial Hypertension

Abstract: Meth-APAH is a severe and progressive form of PAH with poor outcomes. Future studies should focus on mechanisms of disease and potential therapeutic considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 35 publications
6
74
0
Order By: Relevance
“…Another significant unanswered question is whether stimulants may serve as secondary insults in at‐risk children and young adults with attention deficit disorder, especially given the increased use and growing recognition of amphetamines as a cause of pulmonary hypertension (Zamanian et al . ), though this remains largely untested. The decreased vascular density, vascular remodelling and epigenetic modifications that follow perinatal pulmonary vascular insults likely make these individuals uniquely susceptible to stressors later in life, and future studies should address this potential synergy.…”
Section: Increased Susceptibility To Late Pulmonary Vascular Insultsmentioning
confidence: 99%
“…Another significant unanswered question is whether stimulants may serve as secondary insults in at‐risk children and young adults with attention deficit disorder, especially given the increased use and growing recognition of amphetamines as a cause of pulmonary hypertension (Zamanian et al . ), though this remains largely untested. The decreased vascular density, vascular remodelling and epigenetic modifications that follow perinatal pulmonary vascular insults likely make these individuals uniquely susceptible to stressors later in life, and future studies should address this potential synergy.…”
Section: Increased Susceptibility To Late Pulmonary Vascular Insultsmentioning
confidence: 99%
“…2 A 2017 90-patient prospective cohort study from Stanford University also found a strong association and characterized presentations and prognosis of meth-APAH. 3 The mechanism of meth-APAH is not known, but is presumed due to the similarities in chemical structure between methamphetamine and anorexigens, with both having activity at serotonin receptors. 4 Patients with PH and RV failure have been postulated to have a survival benefit if they have a coexisting PFO.…”
Section: Discussionmentioning
confidence: 99%
“…The first prospective cohort study conducted to examine the relationship between Meth and PAH was conducted by our group in 2017 (37). We compared the clinical presentation, disease characteristics, and outcomes of patients with Meth-APAH.…”
Section: Methamphetaminementioning
confidence: 99%
“…Two of these patients had RA, one had PA and one had an undiagnosed arthritis. Of the reported cases, pre-capillary PH was confirmed in all patients (mPAP [35][36][37][38][39][40][41][42][43][44][45][46][47][48] and the pulmonary pressures improved in all patients at 2-4 month follow up after discontinuation of drug. Three of the four were found to have improvement in their PA pressures with addition of PAH therapies while one of the RA cases improved with discontinuation of leflunomide and washout with cholestyramine alone (136).…”
Section: Leflunomidementioning
confidence: 99%